BLINDNESS IN HADITH: TYPOLOGY OF LECTURERS' VIEWS ON HADITH ABDULLAH BIN UMMI MAKTUM IN SUNAN ABŪ DĀWŪD PERSPECTIVE OF DISABILITY PARADIGM - Muhammad Solihin; Ahmad Fudhaili (SOSIOEDUKASI, 2026)
Despite growing scholarship on disability in Islam, little attention has been paid to how classical hadith commentators conceptualize visual impairment through their interpretations of prophetic traditions. This study addresses this gap by analyzing the perspectives of hadith commentators (shurrāḥ al-ḥadīth) on visually impaired persons through the hadith of Abdullah ibn Umm Maktum in Sunan Abū Dāwūd and reconstructing a typology of their interpretations using the disability paradigm as an analytical framework. This study employed library research with an interpretative and comparative approach. Primary sources consisted of Sunan Abū Dāwūd, Sharḥ Sunan Abī Dāwūd by Ibn Raslān, Sharḥ Sunan Abī Dāwūd by 'Abd al-Muḥsin al-'Abbād, and Badhl al-Majhūd fī Ḥall Sunan Abī Dāwūd by Khalīl Aḥmad al-Sahāranfūrī. Data were collected through documentation and takhrīj bi al-lafẓ and analyzed using content analysis, comparative analysis, and interpretation based on the disability paradigm. The findings indicate that all three commentators agree that visual impairment does not prevent a person from serving as an imam, although they employ different interpretive emphases. Ibn Raslān represents an Inclusive-Legitimative typology through his emphasis on prophetic recognition of competence, al-'Abbād develops an Inclusive-Accommodative typology by highlighting practical support for religious participation, and al-Sahāranfūrī constructs an Inclusive-Dialogical typology through the presentation of diverse scholarly opinions. Collectively, these typologies reflect the principles of the Inclusion Model by recognizing the religious authority, participation, and dignity of persons with visual disabilities. This study contributes to hadith scholarship by introducing the disability paradigm as a framework for interpreting classical hadith commentaries and by proposing a conceptual typology that enriches contemporary Islamic disability studies.